2018
DOI: 10.4236/jbm.2018.61006
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Antibacterial Effects of 6-Deoxy-6-Aminoethyleneamino Cellulose

Abstract: Recently, there is a need of alternatives to antibiotics due to increasing antibiotic-resistant microorganism. Promising classes of bioactive polymers are 6-deoxy-6-amino cellulose derivatives. The purpose of the study was the assessment of the biocompatibility of 6-deoxy-6-aminoethyleneamino cellulose (AEAC) with different degree of substitution (DS). HaCaT keratinocyte cell viability was analyzed by measuring the cellular ATP content. The antibacterial activity against Staphylococcus aureus and Klebsiella pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Literature survey showed Finger S et al reported 6-deoxy-6aminoethyleneamino cellulose with different degree of substitution (DS) via tosylation against keratinocyte cell (HaCaT). Their studies concluded that lowest DS (0.3) was most biocompatible with (HaCaT) [ 60 ]. While in another study, El-Sayed et al carried out cytotoxic studies against BJ1 of 3-aminopropyltrimethoxysilane and TiO 2 grafted tosylated cellulose.…”
Section: Resultsmentioning
confidence: 99%
“…Literature survey showed Finger S et al reported 6-deoxy-6aminoethyleneamino cellulose with different degree of substitution (DS) via tosylation against keratinocyte cell (HaCaT). Their studies concluded that lowest DS (0.3) was most biocompatible with (HaCaT) [ 60 ]. While in another study, El-Sayed et al carried out cytotoxic studies against BJ1 of 3-aminopropyltrimethoxysilane and TiO 2 grafted tosylated cellulose.…”
Section: Resultsmentioning
confidence: 99%